Link between Employees’ Locus of Control, Job Satisfaction, and Job Stress among Teachers: A Survey Analysis in Osun State of Nigeria - Olonade, Zaccheaus Olufunminiyi; Ajibola, Kolawole Sunday; Oyewumi, Omotoye Oluwatobi; Olusesi, Lateef Damilare; Bamidele, Damola Esther (Quest Journal of Management and Social Sciences, 2020)
Background: Locus of control relates to generalized expectations of an individual about the location of command over subsequent occurrences. Generally, there are two types of locus o control: internal and external. Locus of control impacts to the job satisfaction and motivation of employees towards the work. Objective: The study aims to examine the link between employees’ locus of control, job satisfaction and job stress. Methods: Simple random sampling technique was used to select four-hundred respondents from different cadres of teachers from primary and secondary schools in Osun State of Nigeria. Data were collected through a structured questionnaire having three scales including personal data. Findings: The results shows that two hypotheses were tested and the results showed that there was a significant relationship between locus of control and employee’s job satisfaction at 0.05 level of significance. Also, it was found out that locus of control significantly predicted employee’s job stress. The study revealed that locus of control has an impact on employee’s job performance and job stress among teachers of Osun State of Nigeria. Conclusion and Recommendations: The study, therefore, recommended that the ministry of education in Osun State has to organize special training on the locus of control for her workforce. Human resource managers should include locus of control as one of the factors that should be measured during recruitment and selection exercise. Furthermore, workers need to be exposed to the outside world which in turn will have an impact on their view of the world and thereafter enhance their locus of control. Implications: The paper will be useful to concerned authority in order to plan the motivation schemes for teachers in Nigeria which would lead to improve situation of job satisfaction among teachers.